Prevalence of Mendelian Trait among Scheduled Caste of Patna (Bihar): - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The discipline of human population biology incorporates study of biology and environmental factors, as well as the forces of micro-evolution leading to macro-evolution which ultimately influence the biological structure of human populations. The unit of study in understanding variations in man is a ‘breeding population’ sometimes also referred to as ‘Mendelian population’. India is inhabited by people of great diversity, different creeds and customs forming what may be designated as multiple (or plural) society. There are about 3000 castes in India, some have genesis in castel stock while others are occupational, linguistic, religious and territorial entities. Each caste is a social unit or what may be called ‘monopolistic guild’ in itself. All these groups are not entirely independent usually people belong to two or more of such groups at the same time. The climate of India has many regional variations determined by locations, altitude, distance from the sea or the mountains and the general relief. India is divided into eight climatic regions based on the monthly value of temperature and precipitation. India is a Union comprising 25 States and 7 Union Territories and these may be categorized into six zones (North, West, East, Central, South India and Islands).The present paper aims at investigating, from the data collected on the basis of information received through the present study on the four endogamous Scheduled Caste populations in and around the District of Patna (Bihar), namely Dushada, Chamars, Pasis Mushars, regarding the prevalence of certain bio-genetic traits among them.